National identity and nineteenth-century Franco-Belgian sculpture. - Wijnsouw, Jana (New York : Routledge, 2018)
This book elaborates on the social and cultural phenomenon of national schools during the nineteenth century, via the less-studied field of sculpture and using Belgium as a case study. The role, importance of and emphasis on certain aspects of national identity evolved throughout the century, while a diverse array of criteria were indicated by commissioners, art critics, or artists, that supposedly constituted a 'national sculpture.' By confronting the role and impact of the four most crucial actors within the artistic field (politics, education, exhibitions, public commissions) with a linear timeframe, this book offers a chronological as well as a thematic approach. Artists covered include Guillaume Geefs, Eugene Simonis, Charles Van der Stappen, Julien Dillens, Paul Devigne, Constantin Meunier, and George Minne.
boek
Keywords: Sculpture, Belgian -- 19th century